(untitled) (Efficient: Indonesian Journal of Development Economics, 2024)
Free exchange plays an important role in economic growth. One of them is the export potential that brings profits. Indonesia is becoming one of the largest producers of crab in the world. The research aims to determine the competitiveness of Indonesia’s and its competitors’ exports in the Asian and world markets, as well as its competitive position and trade specialization index in Indonesia. The data used in the study are secondary data from nine of the world’s largest cranberry producers such as Indonesia, Malaysia, Sri Lanka, China, Madagascar, Tanzania, Comoros, Kenya and Grenada during the period 2013-2022. Data is obtained from UN Comtrade, FAOSTAT, BPS. Competitiveness is measured using Revealed Comparative Advantage (RCA), Reveled Symmetric Comparative Avantage (RSCA). Indonesian Trade Specialization Index using ISP and Export Product Dynamic (EPD) is used to determine competitive position. The results show that Indonesia has a high RCA index but still lags behind Madagascar, Comoros, Tanzania in terms of exports in the world market. While in the Asian market, Indonesia occupies the second position after Sri Lanka. ISP ratings show that Indonesia is at 4 stages and EPD ratings indicate that Indonesia, Madagascar, Grenada, Comoros, and China are in Rising star position while others are in Lost Oppurtunity position. To increase competitiveness and suppress high imports, governments must have the courage to take policies that are appropriate to the conditions and problems that exist.